Does financial liberalization influence saving, investment and economic growth? Evidence from 25 emerging market economies, 1973 - 96 - Niels Hermes; Robert Lensink (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
This paper aims to investigate the relationship between financial liberalization on the one hand and saving, investment and economic growth on the other hand, using a new dataset for measuring financial liberalization for a sample of 25 developing economies over the period 1973-96. We find no evidence that financial liberalization affects domestic saving and total investment (although there are some signs to believe that liberalization may actually reduce rather than increase domestic saving), whereas it is positively associated with private investment, as well as with per capita GDP growth. We find a negative relationship between financial liberalization and public investment. These results suggest that financial liberalization leads to a substitution from public to private investment, which may contribute to higher economic growth.
Keywords: O16; 330; financial liberalization; saving; investment; economic growth; Kapitalmarktliberalisierung; Sparen; Investition; Wirtschaftswachstum; Schwellenländer